iOS forensic analysis for iPhone, iPad and iPod touch - Morrissey, Sean.; Safari eBooks ([Berkeley, Calif.] : Apress ; New York : Distributed to the book trade worldwide by Springer Science+Business Media, 2010)
"iOS Forensic Analysis provides an in-depth look at investigative processes for the iPhone, iPod Touch, and iPad devices. The methods and procedures outlined in the book can be taken into any courtroom. With iOS information never published before and data sets that are new and evolving, this book gives the examiner and investigator the knowledge to complete a full device examination that will be credible and accepted in the forensic community"--Provided by publisher.
History of Apple mobile devices -- iOS operating and file system analysis -- Search, seizure, and incident response -- iPhone logical acquisition -- Logical data analysis -- Mac and Windows artifacts -- GPS analysis -- Media exploitation -- Media exploitation analysis -- Network analysis.
Includes index.
Description based on print version record.
Keywords: iOS (Electronic resource); Application software -- Development; iPhone (Smartphone) -- Programming; iPod touch (Digital music player) -- Programming; iPad (Computer) -- Programming; Mobile computing; Electronic books